A history of multiple concussions does not confer long-term impairments to dynamic cerebral autoregulation. Issue 11 (25th May 2017) - Wright, Alexander D; Smirl, Jonathan D; Fraser, Sarah K; Bryk, Kelsey; Donkelaar, Paul van
Abstract : Objective: To examine the effects of concussion history on an index of cerebral autoregulation in a healthy athlete population. Design: Retrospective Cohort. Setting: Laboratory. Participants: 136 male contact sport athletes (19.1±1.4 years, 66 football, 70 hockey) were recruited; 39 presented with 0 previous concussions, 16 with 3+ previous concussions; exclusion criteria included history of concussion within 6 months. Intervention: Participants completed baseline testing prior to the athletic season. Squat-stand manoeuvres at 0.05 and 0.10 Hz were used to enhance blood pressure (BP) variation. BP and cerebral blood velocity (CBV) in the middle cerebral artery were indexed non-invasively via finger photoplethysmography and transcranial Doppler ultrasound, respectively. Independent variables included sport (2) and concussion history (2). Outcomes: Transfer function analysis point estimates at 0.05 and 0.10 Hz characterised the coherence (correlation), phase (synchronisation), and gain (amplitude buffer) between BP and CBV waveforms during the squat-stand manoeuvres. Results: These findings suggest that, despite reductions in 0.10 Hz phase lead being reported acutely after concussion, multiple concussions do not appear to induce long-term impairments in dynamic cerebral autoregulation metrics. This is an important revelation as it indicates that the cerebrovasculature is able to adequately recover following the acutely diminished buffering capacity associated with a concussive injury Conclusions: These findings suggest that, despite reductions in 0.10 Hz phase lead being reported acutely after concussion, multiple concussions do not appear to induce long-term impairments in dynamic cerebral autoregulation metrics. This is an important revelation as it indicates that the cerebrovasculature is able to adequately recover following the acutely diminished buffering capacity associated with a concussive injury Competing interests: None.